Identification of dropout reasons in young competitive swimmers - Salguero, A.; Gonzalez-Boto, R.; Tuero, C.; Marquez, S. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The purpose of this study was to examine reasons for discontinuing sport participation in Spanish competitive swimmers. Methods: Sixty-two swimming dropouts (40 males and 22 females, ranging in age from 14 to 30 years) were administered the Questionnaire of Reasons for Attrition of Gould et al. Results: The results of the survey indicated that having other things to do was the most important reason for attrition. Other items rated important were related to lack of fun, perception of failure or low skill, while low ratings were given to items related to achievement/status or affiliation. A significant multivariate effect was obtained for gender and for experience at dropout. Analysis of individual items by ''t''-test demonstrated that females placed greater emphasis than males on excessive pressure, hard training, dislike of competition, not winning enough and not feeling important enough. Former swimmers with less experience at dropout rated interest in another sport as more important and being too old as less important than swimmers with more experience. Conclusion: The results of this study support the importance of negative factors related with aspects of the athletic environment that lead to discontinuing in competitive swimming.